Effect of milk yield-based selection on some reproductive traits of Holstein Friesian cows on large-scale dairy farms in Malawi - Chagunda, Mizeck G.G.; Bruns, E.W.; Wollny, C.B.A.; King, H.M. (2004)
This paper describes a study aimed at evaluating the effect of selecting sires based on their breeding values for milk yield estimated in their countries of origin on reproductive performance of their daughters on large-scale dairy farms in Malawi. To do this an analysis was done using 2362 records of purebred Holstein Friesian cattle kept in Central and Southern Malawi from 1986 to 1996. Fixed effects of sire group, herd, year and season of calving were tested and random effects of dam and cow were included in the statistical model applied. (Co)variance components were estimated through the restricted maximum likelihood (REML) procedure. Mean number of services per conception (NSC) was 1.50, gestation interval (GI) was 277days, calving interval between first and second parity (CI1) was 416 days, calving interval between second and third parity two and three (CI2) was 408 days, and age at first calving (AFC) was 32.5 months. In general the majority of the reproductive traits were affected by the non-genetic factors of herd, year and season. Sire group, a proxy of the breeding strategy, had a significant effect on AFC (p<0.01) and CI2 (p<0.05). Factors that had significant effects (p<0.01) on most of the reproductive traits in the study were herd, year of insemination, year of calving, and season of insemination. Phenotypic correlation between NSC and AFC was 0.19, between NSC and GI was -0.05, while that between NSC and CI2 was 0.14. Heritability estimates for NSC, GI, CI1, and AFC were, 0.04, 0.10, 0.001, and 0.20, respectively. The high variation due to non-genetic factors and the low heritability estimates for the reproductive traits indicate that much improvement could be made through improved management, husbandry practices, and strategically utilizing environmental factors.